Universally Designing the Public Sector Workplace: Technology as Disability Access. Issue 1 (11th March 2013) - Basas, Carrie Griffin
<x xml:space="preserve">Abstract</x> More than twenty years after the passage of the Americans with Disabilities Act, people with disabilities continue to face discrimination in society, particularly in employment. At the same time, workers with disabilities often seek shelter in public sector employment settings where job benefits and stability are perceived to be greater. Understanding that employees with disabilities are an increasing and desirable part of the American workforce, unions, particularly in the public sector, have increased outreach to this population. Their collective bargaining agreements will have to reflect this inclusion, however, to be successful in hiring and retaining worker‐members with disabilities. Building on her earlier study of the American Federation of State, County and Municipal Employees (AFSCME)'s collective bargaining agreements and their disability provisions, the author provides a foundation for how unions might adopt proactive, partnership‐based disability policies, particularly in the area of technology‐based reasonable accommodations.